Advanced pancreatic cancer with KRAS wild-type and EGFR-sensitive mutation respond favorably to furmonertinib: A case report - Ma, Xiaoting; Liu, Xiu; Ou, Kai; Zhang, Manman; Gao, Lizhen; Yang, Lin (Frontiers in Oncology, 2023)
Pancreatic cancer is the leading cause of cancer death, and treatment options are limited and mostly ineffective. The patient we report had an EGFR exon 19 deletion and had disease progression in the short term after receiving three front-line treatment regimens. We administered furmonertinib and observed tumor shrinkage, decreased CA19-9. The progression-free survival (PFS) of furmonertinib was 4.7 months, and no adverse effects were observed. However, the patient did not benefit from subsequent nimotuzumab-based therapy. Targeted therapy driven by the detection of genetic signatures in this patient shows potential clinical benefit in refractory advanced pancreatic cancer.